Sistema de gestão da qualidade de escolas da rede Sinodal e seus resultados - Leonhardt, Seno (2005)
This work has the purpose of answering the question: Do quality programs improve the management and the indicators of educational institutions? Objectives were elaborated from this question to effectuate it. The general objective is To develop a system of management for Education Institutions of Rede Sinodal based on the Criteria of Programa Gaúcho de Qualidade e Produtividade (PGQP). Instruments had been elaborated (questionnaires) to evaluate parents, students, teachers and employees satisfaction in relation to the various services and processes developed in 5 schools which belong to the Rede Sinodal de Educação, equivalent to 10% of the total of schools from Rede Sinodal. A diagnostic spreadsheet was elaborated to raise information that has the aim to complement the basement for the creation of indicators. A set of indicators was created that made the performance analysis of institutions possible, the comparison with similar ones and the comparison with official indicators or of institutions of reference. With the information of evaluations and the indicators comparisons the sectors and best services with the practical ones had been identified. These were the support for the elaboration of the Management System that is the main objective of this work. The instruments and the management system had been structuralized from the study of eight criteria of PNQ (Programa Nacional da Qualidade), level of Programa Gaúcho de Qualidade e Produtividade.